2003
DOI: 10.1002/jmv.10354
|View full text |Cite
|
Sign up to set email alerts
|

Mutational patterns of paired blood and rectal biopsies in HIV‐infected patients on HAART

Abstract: Blood and concurrent rectal biopsy samples of human immunodeficiency virus type 1 (HIV-1)-positive highly active antiretroviral therapy (HAART)-treated patients were tested for genotypic resistance by direct sequencing of reverse transcriptase (RT) and protease (PR) regions to compare the patterns of resistance in these compartments. Fourteen subjects (five with undetectable plasma viral load (pVL) and nine persistently viremic) were studied. Four of five patients with undetectable pVL also had undetectable mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…CLAYTON et al (8) documentaram progressão qualitativa e quantitativa nas alterações vistas na mucosa retal de indivíduos infectados pelo HIV, a qual se correlacionou com a presença e a quantidade do vírus no tecido colônico, sugerindo, além da enteropatia do HIV anteriormente comentada, que a mucosa intestinal poderia constituir local de proliferação e de destruição de linfócitos. Mais recentemente, MONNO et al (21) , comparando amostras de HIV obtidas concomitantemente do sangue e de tecido retal, verifi caram padrões de resistência aos anti-retrovirais diferentes, dando suporte à idéia de evolução genotípica variável do HIV nos diferentes compartimentos corporais e enfatizando a participação da mucosa intestinal na seleção do genótipo do HIV.…”
Section: Discussionunclassified
“…CLAYTON et al (8) documentaram progressão qualitativa e quantitativa nas alterações vistas na mucosa retal de indivíduos infectados pelo HIV, a qual se correlacionou com a presença e a quantidade do vírus no tecido colônico, sugerindo, além da enteropatia do HIV anteriormente comentada, que a mucosa intestinal poderia constituir local de proliferação e de destruição de linfócitos. Mais recentemente, MONNO et al (21) , comparando amostras de HIV obtidas concomitantemente do sangue e de tecido retal, verifi caram padrões de resistência aos anti-retrovirais diferentes, dando suporte à idéia de evolução genotípica variável do HIV nos diferentes compartimentos corporais e enfatizando a participação da mucosa intestinal na seleção do genótipo do HIV.…”
Section: Discussionunclassified
“…The time to obtain HIV RNA undetectability in blood plasma, defined as the period between initiation of cART and the first viral load value <40 copies/mL, was 4 months [2,3,4,5,6,7,8,9,10,11,12,13,14,15]. No viral rebound was observed during the study period except 1 blip in patient 4 at month 18 after starting cART.…”
Section: Resultsmentioning
confidence: 99%
“…The rectal mucosa can integrate HIV-1 strains resistant to antiretroviral treatment selected during therapy and participates to the failure to reach optimal local drug concentrations [7,9,10]. Josefsson et al [3] showed that HIV-1 DNA integrated in GALT-infected T cells remains stable during suppressive cART when sequences between plasma sampled at the time of initiation of cART and GALT biopsies obtained 8-12 years after starting therapy were compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At testing, 21% of these anti-HIV-positive women had syphilis, 18.4% gonorrhoea, and an additional 5.2% gardnerella vaginosis. DNA was extracted from the HIV-positive bloodspots (QIAamp DNA blood Mini kit, Quiagen, Germany), and amplification of the pol gene was performed using an ''in-house'' protocol [Monno et al, 2003]. Thereafter, the PCR products were directly sequenced (BigDye Terminator Cycle Sequencing Kit, Applied Biosystem, Foster City, CA).…”
Section: Short Reportmentioning
confidence: 99%